Micro-displacement sensor with multimode fused coupler and concave mirror - Harun, Sulaiman Wadi; Yasin, Moh; Ahmad, Harith (IOP Publishing, 2011)
Fiber optic displacement sensor is demonstrated using a multimode fused coupler probe and a concave mirror target. It is observed that a focal length of the concave mirror make a significant influence to the displacement response, which illustrates three linear slopes with the second slope peaks at the position that is in vicinity of two times of the focal length. The highest sensitivity of 0.56 mV/mm is obtained with an infinity focal length and it is decreased as the focal length of the concave mirror decreases. The widest linear range of approximately 3.3 mm is observed in the third slope region with focal length of 6.0 mm. The highest linear range obtained with the use of 50:50 coupler.